PENERAPAN METODE FORWARD CHAINING TERHADAP SISTEM PAKAR MENDIAGNOSA PENYAKIT DAN HAMA PADA TANAMAN SUKULEN BERBASIS ANDROID - Matthew Richard Arianto (2023)
During the Covid-19 pandemic, succulent plants ranked 4th in the most popular ornamental plant category, with a total of 325,200 searches per year. The owner of a relatively new succulent plant also has a lack of knowledge so that he cannot tell if the succulent plant has been infected with a disease or pest which causes the plant to wither to rot and die. Seeing from these problems, it is necessary to evaluate the system and manage it using a technology. The technology to be built uses an android-based application, the Forward Chaining method for decision making, and the ESDLC (Expert System Development Life Cycle) Method in developing the system with the aim of making it easier for users to access and find information related to succulent plant care. With this expert system, it can be used by the general public and succulent plant owners in identifying pests and diseases on succulent plants and can be developed for further research.